THE EFFECT OF FINANCIAL LITERATURE, LIFESTYLE, AND SELF-CONTROL ON CONSUMPTION BEHAVIOR ON ONLINE SHOPPING BY STATE STUDENTS OF STATE UNIVERSITIES IN SURABAYA - Sufatmi, Nanik; Purwanto, Eko (Jurnal Ekonomi Balance, 2021)
Along with the increasingly rapid globalization, economic conditions will continue to develop and progress. One of the impacts of globalization is that human needs are increasing and increasingly diverse. In the current era, shopping centers are starting to spread and are increasing both using online and offline methods and it is undeniable that at this time online shops are becoming a current trend that is in great demand by all people. The development of this era and technology causes people to make purchases not based on a priority scale of needs but on a priority scale of desire or willingness. This study aims to analyze the effect of financial literacy, lifestyle, and self-control on online shopping consumptive behavior. The population in this study were students at State Universities throughout Surabaya. The sample used in the study was 100 people or respondents. The data used in this study is primary data which is data from the questionnaire results from the answers of 100 respondents. The analysis technique in this study uses Partial Least Square (PLS). The results of the study state that financial literacy and lifestyle have a significant positive effect on online shopping consumptive behavior, while self-control does not have an insignificant effect on online shopping consumptive behavior.